2018
DOI: 10.1002/jcb.27812
|View full text |Cite
|
Sign up to set email alerts
|

T helper cells subtypes and their cytokine gene expression affected by carvacrol in sensitized mice administered during sensitization period

Abstract: Th1, Th2, Th17, and Treg cells and their cytokine gene expressions in splenocytes of control mice, ovalbumin sensitized (S), and S treated with dexamethasone and carvacrol during a sensitization period were examined. Th2and Th17 population as well as the gene expression of IL-4, IL-17, and TGF-β were increased, but Th1, Th1/Th2 ratio, the gene expression of IFN-γ and FOXP3 as well as the IFN-γ/IL-4 ratio were decreased in S compared with control group (P < 0.001 for all cases). Carvacrol treatment caused signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
(107 reference statements)
0
11
0
Order By: Relevance
“…Treatment with CAR significantly reduced Th2 and Th17 population as well as gene expression of IL-4, IL-17, and TGF-β but increased Treg cells, Th1/Th2 ratio, gene expressions of FOXP3 and IFN-γ during sensitization period in mice. 38 CAR also increased viral titer compared to the RSV-PBS group, 62 but decreased levels of TLR7, MyD88, NF-κB, and IRF mRNA in virus infected model. 63 The molecular dynamic simulation studies indicated that molecular interactions between CAR and spike protein of SARS-CoV-2 together with the cellular proteases TMPRSS2, showed that the CAR could inhibit the entry of the virus to the host cells.…”
Section: The Immunomodulatory Effects Of Carmentioning
confidence: 80%
“…Treatment with CAR significantly reduced Th2 and Th17 population as well as gene expression of IL-4, IL-17, and TGF-β but increased Treg cells, Th1/Th2 ratio, gene expressions of FOXP3 and IFN-γ during sensitization period in mice. 38 CAR also increased viral titer compared to the RSV-PBS group, 62 but decreased levels of TLR7, MyD88, NF-κB, and IRF mRNA in virus infected model. 63 The molecular dynamic simulation studies indicated that molecular interactions between CAR and spike protein of SARS-CoV-2 together with the cellular proteases TMPRSS2, showed that the CAR could inhibit the entry of the virus to the host cells.…”
Section: The Immunomodulatory Effects Of Carmentioning
confidence: 80%
“…All changes were seen for the plant and its constituents on the mice model of asthma were similar to dexamethasone or inhaled fluticasone propionate. In fact, steroid drugs were not affected Th1 cytokines, and the effects of Z. multiflora and its constituent, carvacrol, on Th1/Th2 imbalance were more specific than standard antiinflammatory drugs, which is the novel findings and strength of the study (Kianmehr, Haghmorad, et al, 2017;Kianmehr, Rezaee, Mahmoudi, Ghorani, & Boskabady, 2019).…”
Section: Experimental Evidencementioning
confidence: 81%
“…Although, notably, the dose of carvacrol and the time of its applying are crucial, its effects could be various in the different study contexts. For example, while Mahmoodi et al showed that carvacrol at the concentration of 5 and 10 (mg/kg) led to a decrease of IFN-γ and increase of TGF-β levels in the experimental autoimmune encephalomyelitis mice (22), Kianmehr et al implicated the opposite effects, in which the level of IFN-γ increased, however, TGF-β decreased in mice that were sensitized by ovalbumin and treated with 75, 150, and 300 µg/mL concentrations of carvacrol (14). Silva Lima et al indicated that carvacrol has no effects on the TNF-α level in the treated mice at a concentration of 50 and 100 mg/kg (12), but the study on the mice that faced the carrageenan-induced hyper nociceptions, showed that carvacrol caused the decrease of TNF-α level (23).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms of immunomodulatory and anti-inflammatory action of carvacrol are not clear completely (12), it has been discovered that carvacrol reduces the recruitment of immune cells, especially neutrophils (13). Furthermore, it has been shown that it increases IL-10 production and the ratio of IFN-γ/IL-4 as well as Th1/Th2 (12,14). Here, we studied carvacrol as an herbal immunomodulator on RSV infection outcome in a mice model.…”
Section: Introductionmentioning
confidence: 99%